Eight days to live - Johansen, Iris (New York : St. Martin's Press, 2010)
Eve Duncan's adopted daughter Jane has been targeted by a mysterious cult who has decided that she has only eight days to live.
Keywords: Artists -- Fiction; Suspense fiction